Frequency of Helicobacter Pylori in Perforated Peptic Ulcer and Associated Risk Factors (Medical Forum Monthly, 2024)
ABSTRACTObjective: To determine the frequency and risk factors of Helicobacter pylori infection in patients diagnosed with perforated peptic ulcer disease.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Surgical Unit Bakhtawar Amin Medical & Dental College, from January 2023 to December 2023.Methods: A total of 384 patients over the age of 12 with peptic ulcer perforation were included. Detailed histories were taken regarding potential causes of peptic ulcers, such as Helicobacter pylori infection, alcohol consumption, current or past significant illnesses, socioeconomic status and use of tobacco in betel nut or chewing form.Results: In our study, the presence of helicobacter pylori was found in 230 (59.9%) patients.It was seen that the presence of helicobacter pylori was higher in males 146 (65.8%) than females 76 (34.2%), (p=0.006). Presence of helicobacter pylori was higher in smokers 56 (70.9%) than non-smokers, 23 (29.1%), (p=0.025). Similarly, presence of helicobacter pylori was higher in betel nut & pan chewing used patients 30 (78.9%), than 8 (21.1%) betel nut & pan chewing not used patients.Conclusion: H. pylori infection was not significantly associated with PPU. However, factors such as alcohol intake and tobacco use were involved in perforation. Therefore, we can conclude that while H. pylori infection is not a risk factor for PPU, it is important to avoid other risk factors.